(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2017)
This contribution is the reworked version of a conference presented in Paris in November 2016 and aims to show a series of pre-textual and epitaxial elements that lay on the groundwork for the establishment of the genetic file of Martyrdom of St. Sebastian by Gabriele D’Annunzio. The material discussed, largely unpublished, highlights the long gestation of the work and its composite nature.